Primary Intravitreal Bevacizumab for Diffuse Diabetic Macular Edema. The Pan-American Collaborative Retina Study Group at 24 Months (2009)
Purpose: To report the 24-month anatomic and Early Treatment Diabetic Retinopathy Study (ETDRS) best-corrected visual acuity (BCVA) response after primary intravitreal bevacizumab (Avastin; Genentech, Inc., San Francisco, CA; 1.25 or 2.5 mg) in patients with diffuse diabetic macular edema (DDME). In addition, a comparison of the 2 different doses of intravitreal bevacizumab (IVB) used is presented. Design: Retrospective, multicenter, interventional, comparative case series. Participants: The clinical records of 115 consecutive patients (139 eyes) with DDME at 11 centers from 8 countries were reviewed. Methods: Patients were treated with at least 1 intravitreal injection of 1.25 or 2.5 mg of bevacizumab. All patients were followed up for 24 months. Patients underwent ETDRS BCVA testing, ophthalmoscopic examination, optical coherence tomography (OCT), and fluorescein angiography (FA) at the baseline, 1-, 3-, 6-, 12-, and 24-month visits. Main Outcome Measures: Changes in BCVA and OCT results. Results: The mean age of the patients was 59.4±11.1 years. The mean number of IVB injections per eye was 5.8 (range, 1-15 injections). In the 1.25-mg group at 1 month, BCVA improved from 20/150 (0.88 logarithm of the minimum angle of resolution [logMAR] units) to 20/107, 0.76 logMAR units (P less than 0.0001). The mean BCVA at 24 months was 20/75 (0.57 logMAR units; P less than 0.0001). Similar BCVA changes were observed in the 2.5-mg group: at 1 month, BCVA improved from 20/168 (0.92 logMAR units) to 20/118 (0.78 logMAR units; P = 0.02). The mean BCVA at 24 months was 20/114 (0.76 logMAR units; P less than 0.0001). In the 1.25-mg group, the mean central macular thickness (CMT) decreased from 466.5±145.2 ?m at baseline to 332.2±129.6 ?m at 1 month and 286.6±81.5 ?m at 24 months (P less than 0.0001). Similar results were obtained in the 2.5-mg group. Conclusions: Primary IVB at doses of 1.25 to 2.5 mg seem to provide stability or improvement in BCVA, OCT, and FA in DDME at 24 months. The results show no evident difference between IVB at doses of 1.25 or 2.5 mg. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article. © 2009 American Academy of Ophthalmology.